2012
DOI: 10.1111/j.1574-695x.2012.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of potential probiotics in a mouse peanut sensitization model

Abstract: Peanut allergy accounts for the majority of severe food-related allergic reactions and there is a need for new prevention and treatment strategies. Probiotics may be considered for treatment on the basis of their immunomodulating properties. Cytokine profiles of probiotic strains were determined by in vitro co-culture with human PBMCs. Three strains were selected to investigate their prophylactic potential in a peanut sensitization model by analysing peanut-specific antibodies, mast cell degranulation and ex v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 40 publications
6
45
0
Order By: Relevance
“…We confirmed a strong strain-specific impact on in vitro cytokine responses of human PBMCs to bacterial strains, as observed previously (14,(23)(24)(25), except for Bifidobacterium strains, which all displayed the same regulatory profile, with high IL-10 secretion and low IL-12 secretion levels. These results are in line with the study of Latvala et al, which showed that IL-10/IL-12 ratios were higher with Bifidobacterium strains than with Lactobacillus strains (26).…”
Section: Discussionsupporting
confidence: 68%
“…We confirmed a strong strain-specific impact on in vitro cytokine responses of human PBMCs to bacterial strains, as observed previously (14,(23)(24)(25), except for Bifidobacterium strains, which all displayed the same regulatory profile, with high IL-10 secretion and low IL-12 secretion levels. These results are in line with the study of Latvala et al, which showed that IL-10/IL-12 ratios were higher with Bifidobacterium strains than with Lactobacillus strains (26).…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, for a given bacterial species, strain-specific immunomodulation of host cells has been reported (30)(31)(32)(33). The activation of NETs by E. coli was shown to compromise intestinal epithelial integrity (34).…”
Section: Discussionmentioning
confidence: 99%
“…While some probiotic studies have demonstrated health benefits in clinical trials and experimental animal models, others have been inconclusive or negative. It is also clear from the literature that probiotic effects are strain dependent (Meijerink et al, , 2012. Furthermore, probiotic trials using the same strain have also generated conflicting results (Kalliomaki et al, 2010), suggesting that (epi-)genetic variation, lifestyle, and microbiota composition may influence responsiveness to probiotics in prevention of allergic disease.…”
Section: Mechanisms Of Immunomodulation By Probioticsmentioning
confidence: 97%
“…Nevertheless, in recent years there has been considerable progress in understanding the mechanisms of probiotic action and in the future this should help to reliably select candidate strains for human trials. The in vivo effects of probiotics include effects on the mucosal barrier, immunity, and suppression of inflammation (Gluck and Gebbers, 2003;Karczewski et al, 2010;Meijerink et al, 2012). It is also possible that probiotic immunomodulation is indirectly linked to the effects of the probiotic strain on the resident microbiota (O'Toole and Cooney, 2008).…”
Section: Mechanisms Of Immunomodulation By Probioticsmentioning
confidence: 98%
See 1 more Smart Citation